EVALUATION OF THE TRAINING PROGRAM ON DEVELOPMENT OF ROUTINE TO RESEARCH FOR REGISTERED NURSE IN NURSING SERVICE ORGANIZATION: MIXED-METHOD EVALUATION RESEARCH - Chintapanyakun, Teepatad; Poolpanitoopatum, Somporn; Soonthornkul Na Cholburi, Chiraphi (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2024)
This mixed-methods evaluation research aimed to evaluate the training program on the development of routine to research (R2R) for registered nurses in nursing service organizations and to study determining guidance for the development program. Ninety-five registered nurses with trained R2R programs and ten key informants were recruited using purposive selection techniques from Ramathibodi Hospital, Mahidol University. The research instruments consisted of two sets: 1) the assessment questionnaire for the training program (input, process, output, and impact) with content validity ranging from .60 to 1.00 and Cronbach’s alpha coefficient reliability ranging from .81 to .89, and 2) an interview form used to interview registered nurses with trained R2R programs. Data were analyzed using descriptive statistics and content analysis. The results showed that: 1) in evaluating the input, process, output, and impact, all aspects were rated as appropriate at a high level and 2) the guidance for the development program of R2R for registered nurses to enhance efficiency and effectiveness included establishing a research clinic, providing nurse mentors with knowledge and capabilities in nursing research, enhancing positive reinforcement skills, and ensuring continuity of progressive evaluation.